Sir Thomas More's Utopia: An overlooked economic classic. (4th March 2019) - Mangeloja, Esa; Ovaska, Tomi
Abstract: Sir Thomas More's Utopia, published in 1516, is a classic work of how to organise a society based on common property. With a unique mix of common property, institutions and sound economic insights, we argue that More built a framework for a society that could be viable in the long run. While the conditions that make Utopia work are quite restrictive, it does provide a sketch of a society where common property may not stifle long‐term development, but is associated with productive workers and people content with their lives.